Open platform, 32‐channel, portable, data‐logger with 32 PGA control lines for wearable medical device development. Issue 16 (1st July 2014) - Gargiulo, G.D.; Bifulco, P.; Cesarelli, M.; McEwan, A.; Wabnitz, A.
Abstract : A compact isolated low‐power 32‐channel 16‐bit data‐logging system around an NXP ARM processor (LPC1768) and four of the linear technology octal analogue‐to‐digital converters (ADCs) LTC1857/58/59 is designed. The system requires only 250 mA when powered at 5 V to run at full power (including a capacitive 2.8 inch touch‐screen display and 32 Gb SHDC SD memory card). The sample rate is configurable up to 1 k SPS per channel as well as voltage dynamic input up to ±10 V; additionally, 32 chip select lines (SPI protocol) individually addressable and controllable while sampling to configure user‐designed programmable gain amplifiers (PGAs) are available. Collaboration is being sought to improve the software capabilities, particularly to enrich the very basic user interface and to add wireless connectivity. The code is available (under the GPL licence) at our repository, the gerber file to reproduce the PCB is available (on the As‐Is basis) on request. The galvanic isolation between the power supply data connection and ADC channels makes the data‐logger also compatible with the main powered PCs, hence it is suitable for the implementation of medical devices at least for the prototyping and initial testing stages.